Life satisfaction of the elderly in Poland in the light of the Social Diagnosis 2011 - Abramowska-Kmon, Anita (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The main aim of the paper was to analyse the subjective well-being of the elderly in Poland, as well as its determinants by use of the logistic regression. The data used come from the 2011 wave of the survey "Social Diagnosis – living conditions and quality of life of Poles". The analyses have shown that men aged 60 years or more had higher subjective well-being than their female counterparts. Subjective life satisfaction of the elderly in Poland decreases with age for women, but for males on the opposite. The elderly in Poland were satisfied the most with the aspects related to their personal life such as children, marriage, relationship with family member and relatives, while they were the least satisfied with situation in the country, life prospects, health status, sexual life, and economical situation of their families. Educational level and health status (measured in terms of disability) had the greatest impact on the sense of happiness. Generally people with the highest level of education had more chances to be happy than those less educated. The probability of happiness among people without disability was higher than among disabled ones. Married people also had bigger odds to be happy.